Pak Teacher Efforts to Build The Character of Christian Young Adult in Disruption Era - Deflita Lumi; Irene Preisilia Ilat; Marsel Tumbelaka (Conference Series, 2020)
Adolescents in their development are very quick to respond to any recent changes, including in the field of information and communication technology. Changes in various fields including science and communication information technology, known as the era of disruption, certainly have positive and negative impacts on society, including youth. It is a challenge for Christian Religious Education to continue to preserve today's youth, better known as millennial generation, to maintain the Christian character within themselves. Through this research, it will be explained how the efforts of Christian Religious Education teachers in shaping Christian youth karkater in the era of disruption. This research was conducted in junior and senior high school at the city of Manado. The study was conducted using a qualitative-descriptive approach with data collection techniques through interviews with PAK teachers, observations in the school environment where the researcher as the main instrument was also a literature study by collecting data and information from various theories of the appropriate research results. Christian Religious Education teachers in schools play an important role in shaping the character of Christian youth so that through a number of steps the efforts in this paper will greatly assist teachers later.